comparative study of Virtual Microscopy versus Traditional Microscopy for introduction into the Histology Curriculum at a Faculty of Medicine - Tanja Prunk; Bogdan Zdravković; Miha Munda (Acta Medico-Biotechnica, 2021)
Purpose: We currently employ traditional microscopy with glass slides for teaching purposes. Here, we performed a pilot survey on the potential implementation of virtual microscopy. Experienced peer tutors were asked to participate in the evaluation of virtual microscopy versus traditional microscopy. Our main objectives were to determine: whether there is a statistically significant difference in time to locating a structure on a glass slide versus a virtual slide, the possible advantages and disadvantages of each microscopy method, and the benefits of virtual microscopy over traditional microscopy (1-3).Methods: Glass slides were scanned with the Aperio ScanScope CS slide scanner for use as virtual slides. Peer tutors were asked to locate the same structures on each glass slide and the corresponding virtual slides. Times needed to locate these structures were individually measured, and a questionnaire (a modified and translated version of the College of Veterinary Medicine, North Carolina State University virtual microscopy survey) on the advantages of practical use of virtual microscopy provided at the end.Results: One sample t-test showed significant differences (p<0.01) in mean time to locate a structure on glass (23.0s) versus virtual slides (12.5s). In commentaries, peer tutors reported a preference for a combination of traditional and virtual microscopy in practical sessions.Conclusions: Assessors considered virtual microscopy easy to use. Time needed to locate a structure on virtual slides was significantly shorter. After additional surveys, we envisage successful implementation of virtual microscopy in conjunction with traditional microscopy in the histology curriculum.